Culinary Books as Information Media Gorontalo Specialty Food Sagela Sauce - A N Fauzi; Wantoro; D R R Purnamasari (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Indonesia is a country that has various tribes in each region, this causes differences in each region such as Gorontalo. Gorontalo’s special food is very diverse, an example is Sambal Sagela. Sambal sagela itself is a sauce made from julung-julung fish that has gone through a smoking process and is processed like processing chili sauce in general. However, although sagela sauce is one of the archipelago’s chili sauces, it is still rare to find literature that fully discusses sagela sauce with different designs. The method applied in this design uses a communication strategy and a creative strategy, where the communication strategy targets the target audience specifically and the resulting creative strategy has an attractive effect that balances the information. This design aims to inform the general public about the sambal sagela as an effort to increase literacy regarding Indonesian chili sauce. The conclusion obtained in this design, by introducing sagela sauce to the public, this will be very useful for preserving the sagela sauce itself and strengthening Gorontalo Province tourism, both for the people of Gorontalo itself in particular, and the Indonesian people in general.